Lactic acid production by immobilized Rhizopus sp. IIUM-G05 in air pulsed ALR using agriculture waste substrates - Alasali, Usame; Azmi, Azlin Suhaida; Karaman, Isa; Alam, Md. Zahangir; Mohamad Puad, Noor Illi (Society for Adancement of Horticulture, 2023)
The demand for lactic acid (LA) in various fields has increased significantly due to its functional properties. Rhizopus sp. IIUM-G05 has been used before to produce lactic acid using various substrates, but the low production yield remains an issue. This is due to the difficulty in finding a suitable low-cost substrate and controlling the fungal morphology during fermentation to maintain high oxygen concentration. Therefore, this study aimed to address these issues by selecting the best substrate for higher LA yield and using loofah immobilized Rhizopus sp. to increase the yield through semi-continuous simultaneous saccharification and fermentation (SSF) in an air pulsed airlift reactor (ALR). The study compared banana peel (BaP) and beet pulp (BeP) as substrates and found that BaP produced a 3-fold higher yield than BeP. To increase LA yield, the study also tested different air pulsation frequencies in loofah immobilized ALR with BaP. The results showed that the 0.0384 s-1 frequency was the best to increase LA yield to 0.091 g/g after three days of fermentation, which was 2.1-fold higher than the free-cell non-pulsed shake flask culture in the first part of the study. SEM images showed that the 0.1667 s-1 frequency resulted in oxygen transfer limitation in the ALR due to irregular formation and trapped BaP particles between mycelium. Overall, this study demonstrates that BaP can be used for LA production by Rhizopus sp., and the air pulsation system with suitable pulsing frequency may help improve production yield by controlling fungal growth inside submerged cultures.